Analisis pembinaan koperasi sebagai program penanggulangan kemiskinan di kabupaten Rokan Hulu - Makmur, Riski; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study wanted to see cooperatives as a coaching analysis of poverty reduction programs in Rokan Hulu district . The problem is the background of this research are :1 . How is the development of a cooperative partner with the company in Rokan Hulu district? 2 . What factors are the bottlenecks in developing cooperative in Rokan Hulu ?This study is a qualitative research , the data collection techniques in this study is a descriptive analysis . This research uses documentation ( observation ) and interviews with key informants as information objects that aim to achieve goals for the sake of getting information in the study . Data used in this study is primary data and secondary data obtained through direct observation and interviews with key informants in this study .Based on the research and discussion that has been the writer explained in the previous chapter are based on the formulation of the problem , the authors conclude that the Cooperative Program in Rokan Hulu is one of the main programs that successfully participate in reducing poverty in Rokan Hulu to create new job opportunities for the community Rokan Hulu .However, this program can not be used as the main government program Rokan Hulu in the alleviation of poverty , because there are other programs that are also successful in reducing poverty in Rokan Hulu .Keywords : cooperatives , local governments , development